2023
DOI: 10.3389/fnagi.2022.1076393
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling age-independent spectral markers of propofol-induced loss of consciousness by decomposing the electroencephalographic spectrum into its periodic and aperiodic components

Abstract: BackgroundInduction of general anesthesia with propofol induces radical changes in cortical network organization, leading to unconsciousness. While perioperative frontal electroencephalography (EEG) has been widely implemented in the past decades, validated and age-independent EEG markers for the timepoint of loss of consciousness (LOC) are lacking. Especially the appearance of spatially coherent frontal alpha oscillations (8–12 Hz) marks the transition to unconsciousness.Here we explored whether decomposing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…We applied a similar method in a previous investigation with a detailed methodic explanation. 19 The following EEG parameters were computed: the spectral edge frequency (the frequency under which 95% of the power is located), the mean power of the power peak in the alpha range (8 to 12 Hz), the alpha peak frequency (the frequency with the highest power within the alpha band), the alpha power difference between baseline and LOC_1/2/15, the mean power of the beta range before decomposition, the mean power of the power peak in the beta range (12 to 30 Hz), beta peak frequency (the frequency with the highest power within the beta band), and the beta ratio. The beta ratio calculation was derived from the method of Rampil: beta ratio = log[(P30 to 47 Hz)/ (P11 to 20 Hz)].…”
Section: Eeg Data and Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We applied a similar method in a previous investigation with a detailed methodic explanation. 19 The following EEG parameters were computed: the spectral edge frequency (the frequency under which 95% of the power is located), the mean power of the power peak in the alpha range (8 to 12 Hz), the alpha peak frequency (the frequency with the highest power within the alpha band), the alpha power difference between baseline and LOC_1/2/15, the mean power of the beta range before decomposition, the mean power of the power peak in the beta range (12 to 30 Hz), beta peak frequency (the frequency with the highest power within the beta band), and the beta ratio. The beta ratio calculation was derived from the method of Rampil: beta ratio = log[(P30 to 47 Hz)/ (P11 to 20 Hz)].…”
Section: Eeg Data and Spectral Analysismentioning
confidence: 99%
“…11,25,26 During the anesthesia-induced transition to unconsciousness, elderly patients also show a reduced power in the alpha range (8 to 12 Hz) compared to young adults. 19 We hypothesized that a postinduction reduced alpha power might be a sign of a vulnerable brain, leading to a higher risk to develop POD. 24 Furthermore, we observed that POD patients exhibit a reduced postinduction beta arousal, associated with a lower spectral edge frequency within the first minute after LOC.…”
Section: Eeg Signaturesmentioning
confidence: 99%
“…In adulthood, β significantly declines with age (Voytek, et al ., 2015; Waschke, Wöstmann and Obleser, 2017) although the physiological origin of this age-related change is unclear. EEG 1/ f measures also display behavioural and clinical relevance, particularly in conditions thought to relate to shifts in E:I balance, such as those affecting attention and behaviour (Waschke et al ., 2021; Robertson et al ., 2019), states of consciousness (Leroy et al ., 2023), and functional recovery from stroke (Leemburg et al ., 2018). Prior to future research utilising 1/ f measures to explore possible atypical brain E:I or as a biomarker in clinical populations, we must first characterise 1/ f measures across the typically developing (TD) lifespan, from infancy to early adulthood (other studies have begun to chart this for later adulthood, see Finley et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the electroencephalogram (EEG) spectral exponent (i.e., exponential decay of power over frequency) has gained increasing attention as a novel marker of consciousness (Colombo et al 2019; Lendner et al 2020; Maschke, Duclos, Owen, et al 2022; Colombo et al 2023; Leroy et al 2023). Especially in the absence of oscillatory peaks – which is a common phenomenon in disorders of consciousness (DOC) – our group has previously demonstrated diagnostic power of the spectral exponent above and beyond oscillatory power (Maschke, Duclos, Owen, et al 2022).…”
Section: Introductionmentioning
confidence: 99%